Pengaruh Latihan Menggunakan Target Gawang dan Ban Motor terhadap Akurasi Tendangan Penalti Siswa SSB Perwira Timur Purbalingga - Chandra Kartika Aji; Tri Rustiadi (Universitas Negeri Semarang, 2023)
A penalty kick is a great opportunity to score a goal in football game if taken accurately. Penalty kick accuracy training can be done with this target practice. This study aims to determine the effect of target goal training and motorcycle tires on the accuracy of penalty kicks.The method used is a quantitative experimental method. The sample of this study was 20 students of Football School Association Perwira Timur Purbalingga who were divided into two experimental groups using the A-B-B-A pattern.Based on the research, the average pre-test of experimental groups 1 was 13.40, post test 20,20, the difference in the mean was 6,80 with tcount = 11,129 ≥ ttable = 2,262. The average pre-test of experimental groups 2 was 13.30, post test 18,60, the difference in the mean was 5,30 with tcount = 6,380 ≥ ttable = 2,262 with a level of = 0.05 then ?? was rejected and ?? was accepted.The conclusion of this study is that there is a significant effect of practicing penalty kick accuracy using goal targets and motorcycle tires on the accuracy of penalty kicks. Training using goal targets has a high effectiveness in increasing the accuracy of penalty kicks compared to training using motorcycle tires targets